Capivasertib and fulvestrant for patients with hormone receptor-positive advanced breast cancer: characterization, time course, and management of frequent adverse events from the phase III CAPItello-291 study - Rugo, H.S. (2024)
Background: Capivasertib is a potent, selective pan-AKT inhibitor. In CAPItello-291, the addition of capivasertib to fulvestrant resulted in a statistically significant (P < 0.001) improvement in progression-free survival over fulvestrant monotherapy in patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer and disease progression on or after aromatase inhibitor-based therapy. Characterization of the capivasertib-fulvestrant adverse event (AE) profile as managed in CAPItello-291 can inform future management guidance and optimize clinical benefit. Patients and methods: Seven hundred and eight patients were randomized 1 : 1 to capivasertib (400 mg twice daily; 4 days on, 3 days off) or placebo, plus fulvestrant, on a 4-week cycle. Dose reductions/interruptions for capivasertib/placebo were permitted (up to two dose reductions). Safety analyses included exposure, AE, and clinical laboratory data and were conducted in patients who received at least one dose of capivasertib, fulvestrant, or placebo. Frequent AEs associated with phosphoinositide 3-kinase (PI3K)/protein kinase (AKT) pathway inhibition (diarrhea, rash, hyperglycemia) were characterized using group terms. AEs were summarized using descriptive statistics; time-to-event analyses were conducted. Results: Safety analyses included 705 patients: capivasertib-fulvestrant (n = 355) and placebo-fulvestrant (n = 350). Frequent any-grade AEs with capivasertib-fulvestrant were diarrhea (72.4%), rash (38.0%), and nausea (34.6%); frequent grade ≥3 AEs were rash (12.1%), diarrhea (9.3%), and hyperglycemia (2.3%). Diarrhea, rash, and hyperglycemia occurred shortly after starting capivasertib-fulvestrant [median days to onset (interquartile range) of any grade: 8 (2-22), 12 (10-15), and 15 (1-51), respectively], and were managed with supportive medications, dose reductions, interruptions, and/or discontinuation. Discontinuation rates were 2.0%, 4.5%, and 0.3%, respectively. Overall, 13.0% discontinued capivasertib due to AEs. Conclusions: Frequent AEs associated with PI3K/AKT pathway inhibition occurred early and were manageable. The low rate of treatment discontinuations suggests that, when appropriately managed, these AEs do not pose a challenge to clinical benefit.